Control of the Gas Flow in an Industrial Directional Solidification Furnace for Production of High Purity Multicrystalline Silicon Ingots - Lijun Liu; Xiaofang Qi; Wencheng Ma; Zaoyang Li; Yunfeng Zhang (International Journal of Photoenergy)
A crucible cover was designed as gas guidance to control the gas flow in an industrial directional solidification furnace for producing high purity multicrystalline silicon. Three cover designs were compared to investigate their effect on impurity transport in the furnace and contamination of the silicon melt. Global simulations of coupled oxygen (O) and carbon (C) transport were carried out to predict the SiO and CO gases in the furnace as well as the O and C distributions in the silicon melt. Cases with and without chemical reaction on the cover surfaces were investigated. It was found that the cover design has little effect on the O concentration in the silicon melt; however, it significantly influences CO gas transport in the furnace chamber and C contamination in the melt. For covers made of metal or with a coating on their surfaces, an optimal cover design can produce a silicon melt free of C contamination. Even for a graphite cover without a coating, the carbon concentration in the silicon melt can be reduced by one order of magnitude. The simulation results demonstrate a method to control the contamination of C impurities in an industrial directional solidification furnace by crucible cover design.